2016
DOI: 10.5664/jcsm.5410
|View full text |Cite
|
Sign up to set email alerts
|

How Reliable Is Self-Reported Body Position during Sleep?

Abstract: Many patients with obstructive sleep apnea (OSA) exhibit worsening event indices while supine. Positional therapy is an option if indices normalize in non-supine sleep. Although several methods are available for patients choosing positional therapy, monitoring adherence remains challenging in part because the reliability of self-reported sleep position is uncertain. We analyzed self-reported sleep position in a sample of 300 patients who underwent clinical polysomnography (PSG) in our center. We found a broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 5 publications
0
11
2
Order By: Relevance
“…This might suggest, instead of subjects' incompliance, that sleeping position is to some extent not under voluntary control. Somewhat inconsistent with McIntyre et al 's findings, Russo and Bianchi's (2016) …”
Section: Introductioncontrasting
confidence: 54%
“…This might suggest, instead of subjects' incompliance, that sleeping position is to some extent not under voluntary control. Somewhat inconsistent with McIntyre et al 's findings, Russo and Bianchi's (2016) …”
Section: Introductioncontrasting
confidence: 54%
“…Device-assisted therapy is important, especially because patients’ self-report of body position during sleep carries substantial uncertainty. 68 By contrast, REM dominance does not as easily translate into clinical care recommendations for therapy, but REM-dominant OSA has been increasingly linked to hypertension, 69 and thus might impact treatment motivation. Insufficient evidence exists regarding REM-suppressing agents as pharmacological therapy for OSA.…”
Section: Resultsmentioning
confidence: 99%
“…While some studies suggest there is high reliability among patients when asked to recall their most common sleep position, 21 other research suggests that self-reported body position may not match position during sleep. 40 Video research has shown people typically change body position an average of 13 times per night. 21 The influence of the "back-to-sleep" campaign on sleep position preference later in life is something this study was not capable of assessing and is a topic for future studies requiring collaboration with fields outside of plastic surgery.…”
Section: Discussionmentioning
confidence: 99%